PENGGUNAAN MEDIA PEMBELAJARAN VISUAL DALAM MENINGKATKAN MOTIVASI BELAJAR BAHASA INGGRIS PADA SISWA SEKOLAH DASAR - Husnaeni Amelia Fatimah; Alya Zalfa Annisa; Amanda Seftiyani; Siti Jubaedah (CV. Denasya Smart Publisher, 2025)
This study aims to describe the impact of using visual learning media on elementary school students' motivation to learn English. The background of the study lies in the lack of student engagement during English lessons, which are often delivered in a monotonous and text-heavy format. The research was conducted at SDN 270 Gentra Masekdas Bandung using a descriptive qualitative approach. The participants consisted of 26 fourth-grade students. Data were collected through three instruments: student evaluation sheets, open-ended questionnaires, and classroom observation forms. The results showed that the use of visual media improved students' understanding of the material, enhanced emotional engagement, and encouraged independent learning and confidence in expressing opinions. Evaluation results indicated that 80% of students achieved a high level of performance. Other findings revealed that visual media fostered a conducive, competitive, and collaborative learning atmosphere. Visual learning media proved to be effective in increasing students' motivation and are recommended for use in English instruction at the elementary level, particularly in the context of 21st-century learning that emphasizes visual and digital literacy.